The Impact of Climate Change on the Variation of Thermal Extreme Indicators at the Lattakia Monitoring Station (Libya Journal of Geographical Studies, 2025)
This research aims to determine the general trend of changes in annual and seasonal averages of temperature (maximum, minimum) at Lattakia station during the period (1980-2023), using simple linear regression analysis, and the arithmetic mean test to find out the significant differences in the variance between two time periods. A number of indicators were also applied to daily temperature data during the period (2006-2023) in order to know the number of frosty, icy and summer days as well as tropical nights, since the repetition of such days has an impact on various aspects of life. The data analysis showed that the general trend of maximum and minimum temperatures is increasing and significant, and a decrease in the number of frosty days and an increase in the number of tropical nights by (14%) was also shown. In addition to the increase in the number of days in which the temperature ranged between (30°-35°) C by (73.9%) and the decrease in the number of days in which the temperature ranged between (35°- 40°) C by (31.4%.(
Keywords: Climate Change; Thermal extremism; Tropical nights; Summer day; Frost day